The role of oligoclonal band count and IgG index in treatment response and disease activity in multiple sclerosis (vol 83,105391,2024) - Taskiran, Esra; Terzi, Murat; Helvaci, Elif Merve; Eser, Meltem Zeycan; Avci, Bahattin; Faruk, Turan Omer; Karaibrahimoglu, Adnan (Elsevier Sci Ltd, 2025)
[Abstract Not Available]